Perspectives on Public Policy Implementation in Developing World Context: The Case of Ghana’s Health Insurance Scheme - Kipo‑Sunyehzi, D.D. (Springer, 2021)
This paper examines factors that affect public policy implementation in developing world context, with some evidence from Ghana. It looks at how public policy design; organisational and individual factors affect implementation. Public policy implementation debate is along with top-down, bottom-up or mixed approaches. The health insurance scheme in Ghana is a home-based initiative of a developing country to provide health insurance cover for all persons resident in Ghana including those who cannot afford to pay-the poor and vulnerable groups. It utilises more qualitative comparative research approach and used public and private health organisations (hospitals/clinics) in analysing policy implementation process. The results show pol icy design and individual factors have more explanatory power than organisational factors. Also, results show more private health organisations received accreditation than the public ones. The public-private collaboration helped to increase policy beneficiaries’ access to healthcare services. But, these implementation challenges exist over-billings, over prescriptions, disagreements over tariffs and no prompt payments for healthcare services. It concludes that the private organisations exhibited more of agency than stewardship in protecting their profit-oriented/external interests.
Research Article
Keywords: Public policy; Implementation; Health insurance; Health facilities; Developing world